Contribution of cyclin d1 (CCND1) and E-cadherin (CDH1) polymorphisms to familial and sporadic colorectal cancer. - Porter, T; Richards, F; Houlston, R; Evans, D; Jankowski, J; Macdonald, F; Norbury, G; Payne, S; Fisher, SA; Tomlinson, I; Maher, E (2002)
The molecular basis for most non-HNPCC familial colorectal cancer cases is unknown, but there is increasing evidence that common genetic variants may play a role. We investigated the contribution of polymorphisms in two genes implicated in the pathogenesis of colorectal cancer, cyclin D1 (CCND1) and E-cadherin (CDH1), to familial and sporadic forms of the disease. The CCND1 870A/G polymorphism is thought to affect the expression of CCND1 through mRNA splicing and has been reported to modify the penetrance of HNPCC. Inactivation of E-cadherin is common in colorectal cancer, and truncating germline mutations have been reported to confer susceptibility to colorectal as well as diffuse gastric cancer. The -160A/C CDH1 polymorphism appears to affect expression of CDH1 and may therefore also confer an increased risk. We found a significantly higher frequency of CCND1 870A allele in 206 familial cases compared to 171 controls (P=0.03). Odds ratios in heterozygotes and homozygotes were 1.7 (95% CI: 1.0-2.66) and 1.8 (95% CI: 1.0-3.3) respectively. The difference was accounted for by an over-representation of A allele in non-HNPCC familial cases (P=0.007). Over-representation of the CCND1 A allele was also seen in sporadic colorectal cancer cases compared to controls but this did not attain statistical significance (P=0.08). No significant differences between the frequency of CDH1 -160A/C genotypes in familial, sporadic colorectal cancer cases and controls were seen, although a possible association between the low expressing A allele and right-sided tumours was detected in familial cases.